Exogenous melatonin protects small‐for‐size liver grafts by promoting monocyte infiltration and releases interleukin‐6. Issue 1 (21st April 2018) - Song, Zhuolun; Humar, Bostjan; Gupta, Anurag; Maurizio, Eleonora; Borgeaud, Nathalie; Graf, Rolf; Clavien, Pierre‐Alain; Tian, Yinghua
Abstract: Defective regeneration of small‐for‐size (SFS) liver remnants and partial grafts remains a key limiting factor in the application of liver surgery and transplantation. Exogenous melatonin (MLT) has protective effects on hepatic ischemia‐reperfusion injury (IRI), but its influence on graft regeneration is unknown. The aim of the study is to investigate the role of MLT in IRI and graft regeneration in settings of partial liver transplantation. We established three mouse models to study hepatic IRI and regeneration associated with partial liver transplantation: (I) IR+PH group: 60 minutes liver ischemia (IR) plus 2/3 hepatectomy (PH); (II) IR+exPH group: 60 minutes liver IR plus extended hepatectomy (exPH) associated with the SFS syndrome; (III) SFS‐LT group: Arterialized 30% SFS liver transplant. Each group was divided into MLT or vehicle‐treated subgroups. Hepatic injury, inflammatory signatures, liver regeneration, and animal survival rates were assessed. MLT reduced liver injury, enhanced liver regeneration, and promoted interleukin (IL) 6, IL10, and tumor necrosis factor‐α release by infiltrating, inflammatory Ly6C+ F4/80+ monocytes in the IR+PH group. MLT‐induced IL6 significantly improved hepatic microcirculation and survival in the IR+exPH model. In the SFS‐LT group, MLT promoted graft regeneration and increased recipient survival along with increased IL6/GP130‐STAT3 signaling. In IL6 −/− mice, MLT failed to promote liver recovery, which could be restored through recombinant IL6. In the IR+exPH and SFS‐LT groups, inhibition of the IL6 co‐receptor GP130 through SC144 abolished the beneficial effects of MLT. MLT ameliorates SFS liver graft IRI and restores regeneration through monocyte‐released IL6 and downstream IL6/GP130‐STAT3 signaling.